The effects of mobility on neighbourhood social ties - Gundi Knies (University of Essex, Institute for Social and Economic Research (ISER), 2009)
This research examines the strength of peoples ties with close neighbours and the sensitivity thereof to changes in residential mobility, access to modes of public and private transport, and changes in the availability of modern communications technologies using the German Socio-economic Panel Study (SOEP). All forms of mobility have increased over time and are negatively associated with visiting neighbours. With further increases in mobility, close neighbours may become less relevant. Nevertheless, presently the incidence of visits with neighbours is sizeable; in contrast to the frequent assertion in the literature that the neighbourhood is of no importance.
Keywords: 330